Islamic Values as Hidden Curriculum in BIPA Instruction: International Student Experiences at an Islamic University - Asri Nuranisa Dewi; Irma Yulita Silviany; Bilkis Aulia Luxfiati (Universitas Cokroaminoto Palopo, 2026)
This study examines how Islamic values operate as hidden curriculum within Indonesian as a Foreign Language (BIPA) instruction at Universitas Islam Bandung (Unisba). While most BIPA research in Indonesia centers on linguistic aspects, this study asks: through what mechanisms do Islamic values permeate language learning without constituting formal curricular content? Using a qualitative case study design, data were gathered from three BIPA classroom observation sessions, an in depth interview with the BIPA lecturer, and field notes documenting interactions with an Algerian international student. Analysis reveals three interlocking mechanisms: (1) Islamic linguistic scaffolding through greetings and faith based expressions; (2) the physical Islamic campus ecosystem, particularly prayer spaces, as adaptation environments; and (3) pedagogical relationships that transcend instructional boundaries. These findings suggest that in Islamic universities, language learning and value socialization occur simultaneously, producing a form of BIPA instruction inseparable from institutional identity. Implications for contextually responsive BIPA curriculum development in Islamic higher education are discussed. This study's contribution is twofold: it introduces Islamic hidden curriculum as a theoretical lens for language classrooms embedded in religious institutions, and it offers an empirical typology of the mechanisms through which this hidden curriculum operates.